The Development of Xmind-Assisted Mind Mapping Worksheets for Expository Writing Instruction - Indah Nur Afifah; Anita Anggraeni; Ratih Inayah (IKIP Siliwangi, 2026)
Grade XI students often struggle to generate and organize ideas logically in expository writing due to limited pre-writing support. Digital mind mapping tools such as XMind may address this gap. This study aims to develop and evaluate the feasibility of an XMind-assisted mind mapping worksheet designed to support students' expository writing skills at a senior high school in Cimahi. This study used a Research and Development (R&D) method with the ADDIE model. The participants consisted of 10 students in the limited trial and 20 students in the field trial. Data were gathered using expert validation sheets, questionnaires, and field notes, then analyzed using descriptive quantitative methods. The worksheet was validated by two expert lecturers based on three aspects: learning objectives, material selection, and assignment use, exercises, and tests, achieving an overall validity score of 83.93%, which falls into the “very valid” category. Furthermore, students responded positively to the use of the worksheet, suggesting higher engagement, enhanced concept organization, and a better knowledge of expository text form. Therefore, the XMind-assisted worksheet is considered valid, practical, and feasible for supporting the teaching of writing skills.